Video Promosi Beasiswa Student Get Student Pada Universitas Raharja - Lusyani Sunarya; Maimunah Maimunah; Kris Budiyanto (UNIVERSITAS RAHARJA, 2020)
The role of promotion in introducing various educational institutions especially at universities is very important, so that the public can get to know the message conveyed. This is evidenced by the growing type of promotion applied at several universities today, such as promotional videos, company profile videos, banners, brochures and others. With the various types of promotions, a university has a wider opportunity to be known by the public. Likewise with Raharja University, one of which has a type of Student Get Student (SGS) scholarship promotion. Raharja University is a private university with a concentration in management and computer science teaching located in Cikokol, Tangerang City. However, the SGS program still does not have its own promotional video. Therefore the SGS promotional video is needed so that the SGS program is increasingly known, especially by Raharja Students themselves and interested in joining the SGS scholarship program. By applying data collection methods and stages of the concept of media production consisting of stages of pre-production, production and post-production. And also using supporting applications, Adobe Photoshop CC 2017 and Adobe After Effect CC 2017. Video This scholarship program SGS is expected to help the marketing department in increasing the target of new student admissions each year.